Postoperative use of somatostatin analogs and mortality in patients with acromegaly. Issue 1 (January 2019) - Postma, Mark R; Wolters, Thalijn L C; van den Berg, Gerrit; van Herwaarden, Antonius E; Muller Kobold, Anneke C; Sluiter, Wim J; Wagenmakers, Margreet A; van den Bergh, Alfons C M; Wolffenbuttel, Bruce H R; Hermus, Ad R M M; Netea-Maier, Romana T; van Beek, André P
Abstract : Objective: To assess the effect of somatostatin analogs (SSAs) on mortality in relation to disease control of acromegaly after pituitary surgery. Design: A retrospective study in two large tertiary referral centers in The Netherlands. Methods: Overall, 319 patients with acromegaly in whom pituitary surgery was performed as primary therapy between January 1980 and July 2017 were included. Postoperative treatment with SSA was prescribed to 174 (55%) patients because of persistent or recurrent disease. Disease control at last visit was assessed by IGF1 standard deviation score (SDS). Adequate disease control was defined as IGF1 SDS ≤2. Univariate determinants of mortality and standardized mortality ratios (SMRs) were calculated for groups with and without SSA at any moment postoperatively and at last visit. Results: In total, 27 deaths were observed. In univariate analysis, determinants of mortality were inadequate disease control (relative risk (RR): 3.41, P  = 0.005), surgery by craniotomy (RR: 3.53, P  = 0.013) and glucocorticoid substitution (RR: 2.11, P  = 0.047). There was a strong trend toward increased mortality for patients who used SSA (RR: 2.01, P  = 0.067) and/or dopamine agonists (RR: 2.54, P  = 0.052) at last visit. The SMR of patients with adequate disease control who used SSA at any moment postoperatively (1.07, P  = 0.785) and at last visit (1.19; P  = 0.600) was not increased. Insufficiently controlled patients had a significantly raised SMR (3.92, P  = 0.006). Conclusions: Postoperative use of SSA is not associated with increased mortality in patients with acromegaly who attain adequate disease control. In contrast, inadequate disease control, primary surgery by craniotomy and glucocorticoid substitution are associated with increased mortality.